Tobacco and other risk factors for esophageal squamous cell carcinoma in Lilongwe Malawi: Results from the Lilongwe esophageal cancer case: Control study. - Bongani Kaimila; Gift Mulima; Chifundo Kajombo; Ande Salima; Peter Nietschke; Natalie Pritchett; Yingxi Chen; Gwen Murphy; Sanford M Dawsey; Satish Gopal; Kamija S Phiri; Christian C Abnet (Public Library of Science (PLoS), 2022)
Objective Esophageal cancer is the second commonest cancer in Malawi, and 95% of all cases are esophageal squamous cell carcinoma (ESCC). Very little is known about the epidemiology of ESCC in Malawi including risk factors. The main objective of the study was to evaluate and describe risk factors of ESCC in Malawi. Methods We conducted a case-control study from 2017 to 2020 at two hospitals in Lilongwe, Malawi and consenting adults were eligible for inclusion. Endoscopy was conducted on all cases and biopsies were obtained for histological confirmation. Controls were selected from patients or their guardians in orthopedic, dental and ophthalmology wards and they were frequency matched by sex, age, and region of origin to cases. An electronic structured questionnaire was delivered by a trained interviewer. Multivariate conditional logistic regression models were used to assess the associations between subject characteristics, habits, and medical history and risk of ESCC. Results During the study period, 300 cases and 300 controls were enrolled into the study. Median age of cases and controls was 56 years and 62% of the cases were male. Among cases, 30% were ever cigarette smokers as were 22% of controls. Smoking cigarettes had an adjusted odds ratio of 2.4 (95% CI 1.4-4.2 p = 0.003). HIV+ status was present in 11% of cases and 4% controls, which resulted in an adjusted odds ratio was 4.0 (95% CI 1.8-9.0 p = 0.001). Drinking hot tea was associated with an adjusted odd ratio of 2.9 (95% CI 1.3-6.3 p = 0.007). Mold on stored grain has an adjusted odd ratio of 1.6 (95% CI 1.1-2.5 p = 0.021). Conclusion Reducing smoking cigarettes, consumption of scalding hot tea, and consumption of contaminated grain, could potentially help reduce the burden of ESCC in Malawi. Further investigation of the association between HIV status and ESCC are warranted.